Local Brass Band in Ratchaburi - Wan-nawong, Therdpong (Rangsit Music Journal, 2023)
This research article concerns the Ratchaburi local brass band, its background, performance circumstances, musicians’ livelihood, and how its traditions are passed on from one generation to the next. The study also addresses its risk of disappearing and solutions for preservation. This qualitative research, collected by document analysis, interview, observation, and focus group discussion conducted on forty bands; the finding are as follows. Local brass bands have existed in Ratchaburi for more than ninety-four years. They provide ceremonial music for auspicious and mournful occasions. The repertoire has been inherited through oral tradition and a rustic form of notation. Band musicians are paid between three hundred and fifty and one thousand bath for a performance. There are generally four performances a month, but the number can increase to ten in the period before the Buddhist Lent. In the past local bands performed more than fifty marches and fifty Thai traditional songs. However, at the present time the number of songs in use decreases dramatically. The authentic performance practice of them runs the risk of disappearing. Their fading popularity affects the well-being of professional band musicians. Solutions are 1) local musicians should rehearse with specialists in marches and traditional songs, and 2) band leaders should have students practice several marches and traditional songs first and perform them more frequently. Due to the preservation project conducted by the researcher, there was an increase in performances of both marches and traditional songs by the bands in Ratchaburi.